Variasi Ukuran terhadap Kekerasan dan Laju Keausan Komposit Epoxy Alumunium-Serbuk Tempurung Kelapa untuk Kampas Rem - Taka, Ario Kristian; Kristianta, FX.; Sholahuddin, Imam (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
The aim of this research was to investigate the influence of the particle size of coconut shell powder on hardness and wear rate om aluminium epoxy based composite. Experimental method was used in this study by using four configurations of particle size. The configuration includes comersial powder and particle size of 300 µm, 425 µ and 600 µm. The results showed that the highest and smallest hardness value obtained by 300 µm of 63.67 kg/mm2 and 600 µm is 41.67 kg, respectively. However, the highest and smallest wear rate obtained by 600 µm is 8,70 x 10-6 gram/s.mm2 and 300 µm is 1,17 x 10-6 gram/s.mm2, respectively. This phenomena occured due to the coconut shell powder size of 300 µm is well and uniformly spread.